Lattice matched Volmer–Weber growth of Fe3Si on GaAs(001)—the influence of the growth rate. (29th October 2019) - Jenichen, B; Cheng, Z; Hanke, M; Herfort, J; Trampert, A
Abstract: We investigate the formation of lattice matched single-crystalline Fe3 Si/GaAs(001) ferromagnet/semiconductor hybrid structures by Volmer–Weber island growth, starting from the epitaxial growth of isolated Fe3 Si islands up to the formation of continuous films as a result of island coalescence. We find coherent defect-free layers exhibiting compositional disorder near the Fe3 Si/GaAs—interface for higher growth rates, whereas they are fully ordered for lower growth rates.